Efficacy of olive leaf extract–containing cream for facial rejuvenation: A pilot study - Rungsima Wanitphakdeedecha (2020)
© 2020 Wiley Periodicals LLC Background: Olive leaf extract (OLE), a naturally extracted product from olive leaves, contains oleuropein and other bioactive phenolic compounds. Oleuropein was identified to have various medical properties. It was also found to inhibit the effects of both acute and chronic UVB-induced skin damage as well as accelerate wound healing activity. Aims: To evaluate the efficacy of olive leaf extract–containing cream on facial rejuvenation. Methods: This is a prospective pilot study with a total of 36 participants, who presented with photoaging skin. All participants applied the olive leaf extract–containing cream (SUPERHEAL™ O-Live Cream, PhytoCeuticals, Inc, USA) to their whole face twice daily for 2 months. Primary outcomes measured in the study were the changes in the biophysical properties of the skin assessed with the following parameters: melanin and erythema index, transepidermal water loss (TEWL), skin hydration, skin pH, sebum level, texture, and wrinkles. Results: After 2 months, TEWL decreased significantly (P =.007) and maintained the results 1 month after discontinuation of the treatment (P =.007). Skin hydration also increased significantly after 2 months (P =.004). Wrinkles improved significantly on all follow-ups (P <.001, P =.001, P =.001, respectively). An image of the skin captured using Visioscan® showed improvement of the skin texture 2 months after treatment. Majority of the participants (64%) noted improvement in their skin texture. Conclusion: Olive leaf extract–containing cream provided benefits on skin rejuvenation in human skin.